Characterization of metal grid-structure reinforced aluminum foam under quasi-static bending loads. (15th October 2017) - An, Yukun; Yang, Siyi; Zhao, Ertuan; Wang, Zongshen
Abstract: This paper investigates the bending property of metal grid-structure reinforced aluminum foam (MGS-AF) prepared by a melt foaming technique. For this purpose, quasi-static three-point bending tests of aluminum foam with and without metal grid-structures (MGSs) were performed. Experimental results indicate that the failure mode of MGS-AF was transformed from a single tensile failure to a combination of both tensile failure and compressive failure. Yield stress improved from 2.92 to 3.81 MPa for traditional aluminum foam to 6.58–8.41 MPa for MGS-AF. Also, a wide amplitude of stress plateau was detected after yield deformation. Additionally, the existence of MGS significantly improved the energy absorption capacity from 3.0 to 37.1–53.1 J and enhanced the specific energy absorption from 0.15–0.17 J/g to 1.34–1.50 J/g under the same deflection of 25 mm.